The Addition of Tomato and Spinach Powder to Semolina Pasta: A Study of the Impact of the Production Process and Cooking on Phenolic Compounds - Silvia Marzocchi; Federica Pasini; Renzo Santi; Maria Fiorenza Caboni (Applied Sciences)
Pasta is a staple food with daily recommended consumption; thus, it can be an excellent vehicle for delivering bioactive compounds like phenols. However, the high-temperature drying process in pasta production, combined with cooking in boiling water, can significantly reduce the concentration of phenolic compounds. This study aimed to enhance the phenolic content of traditional semolina pasta by incorporating tomato and spinach powder into the recipe. High-performance liquid chromatography–electrospray ionization triple quadrupole mass spectrometry (HPLC-ESI-QqQ-MS) was employed to analyse the free and bound phenolic content in the raw materials, as well as in both dried uncooked and cooked pasta. The addition of tomato and spinach powders, known for their high content in bioactive compounds, increased the overall phenolic content of the final enriched pasta by three and two times, respectively, compared to the semolina and whole-wheat semolina pasta. These findings suggest that pasta enriched with tomato and spinach could serve as a functional food with a greater nutritional profile and health benefits through the enhanced delivery of phenolic compounds.